Leveraging the Incidence, Burden, and Fiscal Implications of Unplanned Hospital Revisits for the Prioritization of Prevention Efforts in Pediatric Surgery. Issue 1 (January 2020) - Cameron, Danielle B.; Serres, Stephanie K.; Glass, Charity C.; Milliren, Carly E.; Graham, Dionne A.; Anandalwar, Seema; Thangarajah, Hariharan; Goldin, Adam B.; Hall, Matthew; Rangel, Shawn J.
Abstract : Objective: To characterize procedure-level burden of revisit-associated resource utilization in pediatric surgery with the goal of establishing a prioritization framework for prevention efforts. Summary of Background Data: Unplanned hospital revisits are costly to the health care system and associated with lost productivity on behalf of patients and their families. Limited objective data exist to guide the prioritization of prevention efforts within pediatric surgery. Methods: Using the Pediatric Health Information System (PHIS) database, 30-day unplanned revisits for the 30 most commonly performed pediatric surgical procedures were reviewed from 47 children's hospitals between January 1, 2012 and March 31, 2015. The relative contribution of each procedure to the cumulative burden of revisit-associated length of stay and cost from all procedures was calculated as an estimate of public health relevance if prevention efforts were successfully applied (higher relative contribution = greater potential public health relevance). Results: 159, 675 index encounters were analyzed with an aggregate 30-day revisit rate of 10.8%. Four procedures contributed more than half of the revisit-associated length of stay burden from all procedures, with the highest relative contributions attributable to complicated appendicitis (18.4%), gastrostomy (13.4%), uncomplicated appendicitis (13.0%), and fundoplication (9.4%). Four procedures contributed more than half of the revisit-associated cost burden from all procedures, with the highest relative contributions attributable to complicated appendicitis (18.8%), gastrostomy (14.6%), fundoplication (10.4%), and uncomplicated appendicitis (10.2%). Conclusions and Relevance: A small number of procedures account for a disproportionate burden of revisit-associated resource utilization in pediatric surgery. Gastrostomy, fundoplication, and appendectomy should be considered high-priority targets for prevention efforts within pediatric surgery.